2016
DOI: 10.1002/mrm.26268
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women models analyzed for RF exposure and temperature increase in 3TRF shimmed birdcages

Abstract: Purpose MRI is increasingly used to scan pregnant patients. We investigated the effect of 3 Tesla (T) two-port radiofrequency (RF) shimming in anatomical pregnant women models. Theory and Methods RF shimming improves B1+ uniformity, but may at the same time significantly alter the induced current distribution and result in large changes in both the level and location of the absorbed RF energy. In this study, we evaluated the electrothermal exposure of pregnant women in the third, seventh, and ninth month of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 28 publications
3
73
0
Order By: Relevance
“…In a recent paper , we showed that the tissues surrounding a metallic hip prosthesis exposed to a gradient field (GF) may undergo a nonnegligible heating (up to some degree), as a result of the electromagnetic energy deposited in the implant. Since then, we have realized that in the MR community these results are generally received with some skepticism, probably because of the fact that most of the scientific papers dealing with thermal problems in MRI focus on RF fields . Similarly, the attention of relevant standardization and regulatory bodies is focused solely on RF‐induced heating .…”
Section: Total Joule Losses P (In Watt) Developed Within the Spherementioning
confidence: 99%
“…In a recent paper , we showed that the tissues surrounding a metallic hip prosthesis exposed to a gradient field (GF) may undergo a nonnegligible heating (up to some degree), as a result of the electromagnetic energy deposited in the implant. Since then, we have realized that in the MR community these results are generally received with some skepticism, probably because of the fact that most of the scientific papers dealing with thermal problems in MRI focus on RF fields . Similarly, the attention of relevant standardization and regulatory bodies is focused solely on RF‐induced heating .…”
Section: Total Joule Losses P (In Watt) Developed Within the Spherementioning
confidence: 99%
“…A number of previous studies have investigated via electromagnetic (EM) simulations the SAR experienced both by the mother and the fetus at 1.5T and 3T . Hand et al and Pediaditis et al used a finite integration technique (FIT): the former considered a truncated model of a 28‐wk pregnant woman at 1.5T and 3T, while the latter looked at a whole‐body 30‐wk pregnant female model at fields between 0.3T and 4T.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have extended the SAR analysis to also estimate temperature increases within the mother and fetus using the Pennes Bioheat equation and the thermoregulation model presented by Laakso and Hirata . In the most recent simulation study, Murbach et al investigated the effect of using RF‐shimming on a dual‐transmit 3T system in terms of the SAR and temperature rise both in the mother and fetus at different gestational stages. Their general conclusions were that RF shimming can reduce the local SAR in the mother but conversely can increase the whole‐body SAR and peak temperature in the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…BJR such as oesophagus atresia, should rather be examined at lower field strengths. Tissue heating is also increased at 3.0 T, 44 albeit this heating is not dangerous for the fetus, it is uncomfortable for the pregnant female.…”
mentioning
confidence: 99%